PROFILES OF BURGLARS IN TURKEY AND SOME FACTORS IN THE PROCESS OF CRIMINALIZATION - Bılgın, Rıfat; Kızmaz, Zahir (My University, 2015)
The topic of this study is people who committed the crime of burglary. The goal of the research is todetermine the profiles of people who committed the crime of burglary and to present some factors that affectthe emergence of individuals’ criminal tendencies. The research was carried out on 50 criminals inDiyarbakır closed prison because of the crime of burglary. The research is based on the interpretation of dataand findings obtained from the survey forms conducted on the prisoners in scope of the study and detailedinterviews that were held with them. The obtained findings show that some effects, such as having low socioeconomicposition, existence of some family problems, working on streets at early ages, contacting withchildren on streets that commit crime and have delinquent actions, existence of the potential of associatingwith criminals, using drugs, leaving school and imitating older criminals, are effective in individuals’becoming criminals.
Keywords: Kriminoloji ve Ceza Bilimi